Supervision in Improving the Quality of Educational Administration at SMAN 2 Rejang Lebong - Yuliana, Fera; Warlizasusi, Jumira; Harahap, Emmi Kholilah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
The objective of this paper was to obtain information about supervision in improving the quality of educational administration at SMAN 2 Rejang Lebong. Supervision was carried out for improving the quality of educational administration where the principal of SMAN 2 Rejang Lebong supervised the teachers, especially for the educational administration. Improving the quality of educational administration needed to be carried out to improve the quality of learning in a programmed and planned manner. The principal of SMAN 2 Rejang Lebong supervised every beginning of each semester and at least once per semester. The main procedure taken by the principal of SMAN 2 Rejang Lebong as a supervisor was to make direct observation with the aim of obtaining data objectively, so that the data obtained can be used to analyze the difficulties faced by the teachers. This research used quantitative methods which produced several findings through several statistical procedures or other methods of quantification (measurement). The supervision carried out by the principal could not be separated from coordinating all efforts in the school environment which included: every teacher's effort to self-actualize and participate in improving school activities. Therefore, it was necessary to have directed coordination to support the whole program.